Pathophysiological Changes in the Body of Pregnant Women with Anemia - Vladmirovna, Sarkisova Viktoriya (American Journal of Bioscience and Clinical Integrity, 2025)
Anemia is a condition in which the number of red blood cells or hemoglobin in the blood is reduced. With anemia, the number of red blood cells and hemoglobin in the blood is reduced and the body does not receive enough oxygen (normal blood on the right, anemia on the left). Erythrocytes, or red blood cells, are the most numerous cells in the blood. Their main function is to transport oxygen from the lungs to the tissues. Red blood cells contain hemoglobin, which helps them transport oxygen. One hemoglobin molecule can bind up to four oxygen molecules.